2016
DOI: 10.1016/j.jaci.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

House dust mite–induced asthma causes oxidative damage and DNA double-strand breaks in the lungs

Abstract: This work calls attention to reactive oxygen and nitrogen species and HDM-induced cytotoxicity and to a potential role for DNA repair as a modulator of asthma-associated pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
105
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 57 publications
10
105
1
Order By: Relevance
“…ROS plays a significant role in pollen-induced (7) or HDM-induced (8) allergic sensitization and asthma. Very recent studies have suggested that HDM can directly induce ROS generation, causing oxidative DNA damage and asthma-associated pathophysiology (8,43). Environmental allergens can either directly induce ROS production or promote local inflammatory processes that lead to the secondary production of ROS (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ROS plays a significant role in pollen-induced (7) or HDM-induced (8) allergic sensitization and asthma. Very recent studies have suggested that HDM can directly induce ROS generation, causing oxidative DNA damage and asthma-associated pathophysiology (8,43). Environmental allergens can either directly induce ROS production or promote local inflammatory processes that lead to the secondary production of ROS (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Very recent studies have suggested that HDM can directly induce ROS generation, causing oxidative DNA damage and asthma-associated pathophysiology (8,43). Environmental allergens can either directly induce ROS production or promote local inflammatory processes that lead to the secondary production of ROS (6)(7)(8). Here, we demonstrated that CRE can induce ROS production and that the production was suppressed in ROS-resistant MMVVδ mice, suggesting that ox-CaMKII may participate in a feed forward circuit to increase ROS production in mast cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to allergens may also cause a runny nose, fever, or rash. It has also been shown that dust in people with allergic asthma induces an inflammatory response and increases the production of free radicals, leading to oxidative DNA damage and lipid peroxidation [7].…”
Section: Introductionmentioning
confidence: 99%
“…They are also risk factors for rhinitis [2] and food-induced anaphylaxis [3]. Some other potential activities have been suggested for HDM or their components, for example, oxidative damage to proteins, lipids, and DNA in lung cells [4] or induction of gastrointestinal inflammation by the enzymatic properties of Der p 1 [5]. Molecular studies have been improved by the production of HDM allergens as recombinant molecules, now available for component resolved diagnosis (CDR) and the designing of potential allergy vaccines.…”
Section: Introductionmentioning
confidence: 99%